2017
DOI: 10.1177/1938965516686116
|View full text |Cite
|
Sign up to set email alerts
|

The Matter of Encumbrance: How Management Structure Affects Hotel Value

Abstract: Hotel owners have two fundamental concerns: the financial operating performance of their asset and its selling price. While they often contract a hotel management company to operate the hotel through a lease or management agreement, common industry perception holds that such encumbrance decreases the sales price of hotel real estate assets. This implies that owners who outsource the hotel’s management may be sacrificing a greater selling price in exchange for improved operating results. While this is a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…More recently, Corgel et al (2015) tested two hedonic pricing models to evaluate the relative contributions of property, city, and capital market determinants in a sample of hotel transactions spanning the period from 2005 to 2010, concluding that the inclusion of variables measuring city and capital market effects added little to the explanatory power of the hedonic model. Finally, Hodari et al (2017) employed a hedonic valuation model to investigate the effect of hotel management and lease agreements on market value in a sample of 442 hotel transactions in the United Kingdom between 2000 and 2015. Their results show that hotels encumbered by hotel management agreements and lease agreements sell at a premium relative to unencumbered properties with varying effects across geographic areas and economic periods.…”
Section: Lodging Real Estate Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Corgel et al (2015) tested two hedonic pricing models to evaluate the relative contributions of property, city, and capital market determinants in a sample of hotel transactions spanning the period from 2005 to 2010, concluding that the inclusion of variables measuring city and capital market effects added little to the explanatory power of the hedonic model. Finally, Hodari et al (2017) employed a hedonic valuation model to investigate the effect of hotel management and lease agreements on market value in a sample of 442 hotel transactions in the United Kingdom between 2000 and 2015. Their results show that hotels encumbered by hotel management agreements and lease agreements sell at a premium relative to unencumbered properties with varying effects across geographic areas and economic periods.…”
Section: Lodging Real Estate Researchmentioning
confidence: 99%
“…Distressed hotel research in particular is relatively scarce, with little or no attention paid to liquidation prices of distressed hotels or the characteristics that drive foreclosure discount pricing. Instead, the existing lodging literature has predominantly focused on factors influencing non-distressed hotel values (Corgel, 2007;Corgel et al, 2015;Hodari et al, 2017;O'Neill, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, hotel businesses may have concerns about the risk of rapid obsolescence of new technologies, technological complexity, implementation challenges and the higher requirements of having a more skilled staff and additional technological resources (Dewan et al , 2007; O’Neill and Carlback, 2011). Other risks include the sizeable initial capital cost of the research and development of new technologies (Sorokina et al , 2016; O’Neill and Carlback, 2011), the susceptibility of failure during uncertain market conditions (Mayock, 2011) and increased operating and system maintenance expenses (Hodari et al , 2017). Research has shown that investments in IT in hospitality businesses do not always guarantee a positive impact on hotels’ sales revenues (Melián-González and Bulchand-Gidumal, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Even though these detrimental effects associated with innovation and business outcomes have been empirically scrutinized widely in the manufacturing industry, very little knowledge exists regarding the impact of organizational structure on service innovativeness and the performance of service organizations such as hotels and leisure facilities (Agarwal et al, 2003;Hodari, et al, 2017;Sin, et al, 2005). More specifically, to our best knowledge, relatively few management academics and scholars have conducted research, in the empirical sense, on the proposition of the adoption and confluences of organic structure along inter-functional coordination and learning orientation on service innovation (Chang et al, 2011;Øgaarda et al, 2008;Tajeddini, 2011).…”
Section: Introductionmentioning
confidence: 99%